Chicken Productivity Indicators (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The article presents data and conclusions on live weight indicators and zoohygienic standards of poultry belonging to the Lohmann Lsl -classic chicken crosses in different periods.